The authorship and date of the genus-group name Pachylomera (Coleoptera: Scarabaeidae) - Ziani, Stefano; Branco, Tristão (Zootaxa, 2011)
In 1828, the English entomologist and clergyman William Kirby described Scarabaeus femoralis using material from the collection of another English entomologist and clergyman, Frederick William Hope. The holotype of Scarabaeus femoralis Kirby, 1828 (Fig. 1) is in the Hope Entomological Collections, Oxford University Museum of Natural History (hereafter referred to as OUMNH). The genus Pachylomera was subsequently erected for this species widespread in central and southern Africa. The purpose of this note is to demonstrate, under the rules of the International Code on Zoological Nomenclature (1999), that Griffith & Pidgeon (1831) should be credited with the authorship of the genus-group name Pachylomera.